Islamic boarding school; life skill and social interaction based education to build student’s independence – moderation test - Wahono, Wahono; Hidayah, Nur; Zulkarnain; Endang Sri Radjeki (Jurnal Konseling dan Pendidikan, 2025)
Background of the study: Islamic boarding schools' life skill educational system is applied and integrated using a planned system. Peer interaction in Islamic boarding schools has dramatically impacted how individuals choose their clothes, hobbies, communities, friendships, and other social activities. Additionally, education in Islamic boarding schools gives students independence to survive. Based on these, Aims and scope of paper was conducted to find out the positive influences of life skill education towards the independence of students of a modern Islamic boarding school through peer social interaction. Method. This study was conducted on 212 students of Class VI on the central campus of Darussalam Gontor Modern Islamic Boarding School Ponorogo. The school year is 2021-2022. The subjects were chosen randomly using a random sampling technique with the Krejcie and Morgan formula. The respondent data was obtained from the institution's records and surveys from inventory questionnaires. The validity test used product-moment correlation, while the reliability test used alpha Cronbach. Relatively, this study used the path analysis method. Results. There was a positive impact of life skills on the independence of students of modern Islamic boarding schools, and there is also a positive impact of life skills through peer social interaction towards the independence of students of modern Islamic boarding schools. The results of the F calculation proved all of these hypotheses at 2,361 (p>0,05) and R-squared of 0,430 or 43%. That means that the amount of life skill variable impact (X) and social interaction (Z) on independence (Y) was at 43%. Discussion and Conclusion. Islamic boarding schools' education system and learning process is an education life skill model in which students learn and are trained to solve and overcome various issues they face independently. Independence is built not only by their motivation but also by their environment. Independence can be developed by implementing noble values and conditioning environmental factors such as the learning environment.